Getting dynamic implementation to work - CHEN, Yi-Chun (Institutional Knowledge at Singapore Management University, 2023)
We develop a new class of two-stage mechanisms, which fully implement any social choice function under initial rationalizability in complete information environments. We show theoretically that our Simultaneous Report (SR) mechanisms are robust to small amounts of incomplete information about the state of nature. We also highlight the robustness of the mechanisms to a wide variety of reasoning processes and behavioral assumptions. We show experimentally that a SR mechanism performs well in inducing truth-telling in both complete and incomplete information environments and that it can induce efficient investment in a two-sided hold-up problem with ex-ante investment. The SR mechanism also outperforms a variety of other mechanisms proposed in the literature in terms of both efficiency and truth-telling rates and individuals are willing to use the mechanism when given the choice.